Clarifying the origin of molecular O2 in cathode oxides - Gao, Xu; Li, Biao; Kummer, Kurt; Geondzhian, Andrey; Aksyonov, Dmitry A.; Dedryvère, Rémi; Foix, Dominique; Rousse, Gwenaëlle; Ben Yahia, Mouna; Doublet, Marie-Liesse; Abakumov, Artem M.; Tarascon, Jean-Marie (Nature materials, 2025)
Anionic redox has reshaped the conventional way of exploring advanced cathode materials for Li-ion batteries. However, how anions participate in the redox process has been the subject of intensive debate, evolving from electron holes to O–O dimerization and currently to a focus on trapped molecular O 2 based on high-resolution resonant X-ray inelastic scattering research. Here we show that the resonant X-ray inelastic scattering signal of molecular O 2 is not exclusive to Li-rich oxide cathodes, but appears consistently in O-redox-inactive oxide materials even with a short beam exposure time as low as 1 min, indicating that molecular O 2 species are not directly related to voltage hysteresis and voltage decay. We further demonstrated that molecular O 2 is not a direct product of electrochemistry but more likely a consequence of the core excitation process in resonant X-ray inelastic scattering, for which the possible scenarios of the dissociation of ‘M-(O–O)’-like species on beam excitation must be considered. Collectively, our results reconcile the conflicting reported results on the (non-)observation of molecular O 2 signal collected from different beamlines and suggest that molecular O 2 is not the energetic engine of new battery oxide cathodes. Resonant inelastic X-ray scattering measurements suggest that the oxidized oxygen species in high-energy Li-rich oxide cathodes are trapped molecular O 2 , which is also observed in O-redox-inactive materials. This suggests that resonant X-ray inelastic scattering measurements generate these species, and molecular O 2 is not responsible for voltage hysteresis and decay.